Electronic Transport in Heterostructures of Chemical Vapor Deposited Graphene and Hexagonal Boron Nitride. Issue 12 (3rd November 2014) - Qi, Zhengqing John; Hong, Sung Ju; Rodríguez‐Manzo, Julio A.; Kybert, Nicholas J.; Gudibande, Rajatesh; Drndić, Marija; Park, Yung Woo; Johnson, A. T. Charlie
Abstract : CVD graphene devices on stacked CVD hexagonal boron nitride (hBN) are demonstrated using a novel low‐contamination transfer method, and their electrical performance is systematically compared to devices on SiO2 . An order of magnitude improvement in mobility, sheet resistivity, current density, and sustained power is reported when the oxide substrate is covered with five‐layer CVD hBN.